تقييم مؤشرات أداء البنوك الإسلامية في ظل الأزمة المالية العالمية - abd lkader, abd rahmen; abd lkarim, moumen (Finance and Business Economies Review, 2023)
This paper attempts to address the evaluation of sample performance indicators of Islamic banks in light of the global financial crisis During the period 2005-2012, by studying the indicators of profitability, liquidity, capital adequacy and asset quality. The study concluded that the Islamic banks are characterized by their efficiency, This is a financial crisis, by moving away from forbidden riba-based transactions, and the good results achieved by these banks in the studied indicators before, during and after the global financial crisis. This is compared with the results achieved in conventional banks that have had profound effects on Indicators.